Surface fertigation: a review, gaps and needs - Ebrahimian, Hamed; Keshavarz, Mohammad R.; Playán, Enrique (Spanish Journal of Agricultural Research, 2014)
Surface fertigation is a common choice when it comes to applying fertilizers in surface irrigated crops. The inherent complexity of the concepts and equations governing surface fertigation has made this technique a challenging research issue in the past decades. A number of researchers have used field experiments and/or modelling results to develop recommendations aiming at improving surface fertigation management. In this paper, these recommendations are reviewed and classified considering the particular type of surface irrigation system. Key factors affecting surface fertigation performance, such as the inflow hydrograph, soil and water quality, effective root depth for fertilizer uptake and the specific surface irrigation method are discussed. The history of surface fertigation modelling is reviewed, introducing key developments, accomplishments and open issues. Finally, current research gaps and needs are identified and discussed, such as the coupling of two-dimensional surface and subsurface simulation models or the use of performance optimization approaches. Research gaps require an intensification of modelling and/or experimental efforts.